MAKNA KECANTIKAN PADA IKLAN TELEVISI KOSMETIK BERLABEL HALAL (STUDI KASUS: MAZAYA DIVINE BEAUTY) - Yudhistya Ayu Kusumawati (Fakultas Seni Rupa dan Desain ITB, 2016)
Indonesia is a country that majority Moeslem. About product consumption, Indonesian use halal concept. Mazaya is a halal cosmetic that made from safe fabrics. To persuade their audience, Mazaya campaign it product through television advertisement. As halal cosmetic ad, Mazaya shows unique beauty concept that differ from another cosmetic ad. Mazaya appearing three of brand ambassador that using veil. The purpose of this research is to identify beauty meaning in Mazaya ad. According to the explanation before, this research focuses on beauty aspect. This research use qualitative approach to identify semiotic structure Mazaya ad. Analysis technique in this research used Roland Barthes semiotic analysis to analyze elements of semiotic included signifier & signified, denotation & connotation and myth & ideology.Keyword: beauty, meaning, advertisement, halal cosmetic